Numerical simulation of peristaltic urine flow in a ureter with kidney stone: A two-dimensional axisymmetric study - Adibi, Tohid; Razavi, Seyed Esmail; Mehrejoui, Hossein; Mohtadi-Bonab, M.A. (Edelweiss Applied Science and Technology, 2026)
The peristaltic urge of urine in the ureter is highly significant in the functioning of the kidneys, and how the peristaltic waves and the mobile kidney stones interact is not well comprehended. In this study, the two-dimensional axisymmetric numerical model of this interaction is developed by considering the fluid-structure interaction in COMSOL Multiphysics. The ureter is simulated as a 275 mm deformable tube having a diameter of 5 mm and a 2 mm spherical stone, which is free to move in an axial motion direction. The contraction of the peristaltic is simulated by a sinusoidal wave having an amplitude of 1 mm in 10 seconds. Findings indicate that peristaltic waves produce large pressure differentials on the stone (up to 8.37 Pa) and cause overall stone movement of 3.354 mm towards the bladder. The highest fluid velocity rises almost seven times to 5.99 × 10-3 m/s in the small gap at the stone, which raises the wall shear stress by ten times in comparison with the base (0.423 Pa). It is a local flow reversal that has reverse velocities of -3.12 × 10-4 m/s and lasts 0.41–0.72 seconds. Pumping efficiency analysis indicates that a stone transport averages 10.55% with a high correlation (0.89) between the pressure differential and the displacement of the stone, proving pressure-driven transport to be the most dominant. The results of these studies give a quantitative understanding of the hydrodynamic forces that govern the migration of the stones and the intricate flow regime in the blocked ureter with clinical implications in the management of stone disease.